The importance of geographique information systems in the study of urbain expansion Civil ease study m’sila- Algeria: دراسة حالة مدينة المسيلة الجزائر - Kherkhache , Afaf (Journal of Human Sciences, 2020)
Geographique information systems is a modern technology that has been used in many desciplines in cluding cities and their expansion we used this techniques to study urbain expansion of the city of m’sila ,we resorted to the use of aerial photograph and processed them by means of program arc gis 10.2,for the period(1961- 1996 – 2015 ) and trends in the urbain expansion of the city, and highlight its developement highlighting the effectiveness of these techniques to design digital maps and thematic easy, to deal in the management of the city.